Total factor productivity growth in upper middle income Balkan countries from 2000-2017, total economy and sectoral approach: the growth accounting method - Bacovic, Maja (Publishing House of Wroclaw University of Economics and Business, 2021)
The author estimated TFP in the total economy and at sectoral level (agriculture, industry and services) in seven upper middle-income Balkan countries (Albania, Bulgaria, Bosnia and Herzegovina, North Macedonia, Montenegro, Serbia and Romania) from 2000 to 2017, applying the growth accounting approach. This is the first study presenting estimates on TFP on a sectoral level for a selected group of countries, and also the first study presenting estimates on TFP in the total economy for a selected time period. The sample was selected based on income level and geographic criteria. All countries are ex-centrally planned economies. Although several studies presented growth accounting for Central and Eastern European countries for earlier years, very few presented it for Balkan countries, and none for this time frame and using a sectoral approach. In addition, the time frame was split into two subperiods, 2000-2009 and 2010-2017, to gain a better insight into TFP growth in the earlier transitional phase in each country, and including changes which may occur as the country is moving towards a higher income level. Although some countries from the sample, such as Bulgaria and Romania, made transitional progress earlier than others, the economies of all countries from the sample experienced negative trends during the global financial crisis (2007-2009), so the study included that period in the first subperiod. Other than this, the contribution to the literature is the presented methodology for sectoral TFP computation. The research confirmed the importance of sectoral TFP analysis and subperiod analysis, as variations between TFP in the total economy and at sectoral level are significant, but also between two sub periods
Argumenta Oeconomica, 2021, Nr 1 (46), s. 79-97